RANCANG BANGUN KONTROL SUHU PENYIRAMAN OTOMATIS TANAMAN BERBASIS IOT (STUDI KASUS: TOKO TANAMAN HIAS FUKU FLORA) - Ardian Rizky Ramadhani (CV. Multi Kreasi Media, 2023)
In this era of very rapid technological development, many tools can help humans work automatically. The results of technological developments include the application of IoT for the manufacture of automatic plant sprinklers. Watering plants is something that must be done in plant care activities. Plant care generally consists of watering and fertilizing,this must be done regularly. If not done regularly, it can cause the plant to wither, not grow, and then die. The most important thing is to keep the water content in the plant not reduced or excessive. The purpose of this automatic plant watering device is to help maintain plant water content. This study uses the RnD method. While the components used include Soil Mousture for soil moisture. In addition, it also uses the Blynk application installed on a smartphone as monitoring soil moisture values and watering notifications. The results of watering indicate the categories of plants that need to be watered, including; a lot, moderate, little, and not water. This research produces a tool that can water plants automatically according to the soil moisture sensor with notifications on smartphones.